2022
DOI: 10.7759/cureus.30326
|View full text |Cite
|
Sign up to set email alerts
|

Fertility With Early Reduction of Ovarian Reserve

Abstract: Female infertility is defined as the failure to conceive after a year of frequent, unprotected sexual activity. Infertility affects 8-10% of females worldwide. There are many causes of infertility. One of them is diminished ovarian reserve (DOR). In this condition, the ovary loses its reproductive potential, which affects fertility. This condition may be caused due to injury, but it usually results from aging. DOR is one of the main reasons for infertility in women worldwide. A woman with DOR has fewer eggs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Farhi et al reported that elevated E2 levels during IVF cycles were linked to a higher incidence of adverse pregnancy outcomes [ 27 ]. Lower basal E2 was associated with better pregnancy rates and ovarian reserve during IVF utilizing a gonadotropin releasing hormone (GnRH) antagonist [ 28 ]. Morales et al reported serum E2 on the day of the trigger as a predictor of metaphase II oocytes in antagonist cycles encourage greater oocyte maturity and fertilization [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Farhi et al reported that elevated E2 levels during IVF cycles were linked to a higher incidence of adverse pregnancy outcomes [ 27 ]. Lower basal E2 was associated with better pregnancy rates and ovarian reserve during IVF utilizing a gonadotropin releasing hormone (GnRH) antagonist [ 28 ]. Morales et al reported serum E2 on the day of the trigger as a predictor of metaphase II oocytes in antagonist cycles encourage greater oocyte maturity and fertilization [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol is used as a hormonal supplement to improve symptoms effectively; however, its long-term use can potentially increase the risk of breast cancer and endometrial cancer. 23 Interestingly, traditional Chinese medicine is a very effective method, 5 which has been used for a century and has proven effective in treating DOR because of its obvious clinical efficacy. However, the molecular mechanism by which YLF acts on DOR is still mainly unknown, which severely restricts its use and promotion.…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, it is accepted that the number of growing primordial follicles and the Anti-Mullerian hormone (AMH) secreted from preantral-antral follicles most accurately reflect the size of the follicle pool. 13,14 Comparing the AFC of the operated side ovary with that of the contralateral ovary seems to be the most appropriate approach to assess ovarian reserve. Bozdag et al compared the operated and contralateral ovaries after detorsion in terms of AFC and ovarian volumes, but they could not find a statistically significant difference between the ovaries.…”
Section: Discussionmentioning
confidence: 99%